2020
DOI: 10.1371/journal.pone.0219106
|View full text |Cite
|
Sign up to set email alerts
|

NaV1.1 and NaV1.6 selective compounds reduce the behavior phenotype and epileptiform activity in a novel zebrafish model for Dravet Syndrome

Abstract: Dravet syndrome is caused by dominant loss-of-function mutations in SCN1A which cause reduced activity of Nav1.1 leading to lack of neuronal inhibition. On the other hand, gain-offunction mutations in SCN8A can lead to a severe epileptic encephalopathy subtype by over activating Na V 1.6 channels. These observations suggest that Nav1.1 and Nav1.6 represent two opposing sides of the neuronal balance between inhibition and activation. Here, we hypothesize that Dravet syndrome may be treated by either enhancing N… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…Phenytoin demonstrated effectiveness in decreasing seizure episodes in several patients with SCN8A-related epilepsies, however, side effects during prolonged use are very common (Boerma et al, 2016;Braakman et al, 2017). A recent study of a DS model using zebrafish demonstrated the use of the channel blocking compound MV1312, which is 5-6 fold selectivity of NaV1.6 over NaV1.1-1.7, reduced burst movement phenotype and the number of epileptiform events, activity similar to that described with the use of a selective NaV1.1 activator AA43279 (Weuring et al, 2020). Selective Nav1.6 blockers may represent a new therapeutic strategy for DS patients.…”
Section: Nav16mentioning
confidence: 79%
“…Phenytoin demonstrated effectiveness in decreasing seizure episodes in several patients with SCN8A-related epilepsies, however, side effects during prolonged use are very common (Boerma et al, 2016;Braakman et al, 2017). A recent study of a DS model using zebrafish demonstrated the use of the channel blocking compound MV1312, which is 5-6 fold selectivity of NaV1.6 over NaV1.1-1.7, reduced burst movement phenotype and the number of epileptiform events, activity similar to that described with the use of a selective NaV1.1 activator AA43279 (Weuring et al, 2020). Selective Nav1.6 blockers may represent a new therapeutic strategy for DS patients.…”
Section: Nav16mentioning
confidence: 79%
“…For instance, cannabidiol and GS967 (otherwise known as Prax330) have been shown to preferentially reduce aberrant persistent and resurgent currents over transient sodium currents, however these compounds do not appear to be selective for Na v 1.6 and can target currents in other isoforms, like Na v 1.2 [ 91 , 114 , 115 , 116 ]. More recently, anti-epileptic compound screens in zebrafish models of epilepsy revealed two novel blocking compounds, MV1312 and MV1369 [ 117 ]. Although MV1312 showed a 5–6 fold selectivity of Na v 1.6 over Na v 1.1–Na v 1.7, this compound displays a comparable blocking affinity for Na v 1.8, a major PNS isoform involved in pain sensation.…”
Section: Na V 16 Overviewmentioning
confidence: 99%
“…For example, AA43279 is one small chemically synthetized compound identified in a screening campaign looking for Na v 1.1 activators. AA43279 acts as an inactivation blocker and appears efficient to functionally counteract Na v 1.1 haploinsufficiency in a zebrafish model of Dravet syndrome ( Frederiksen et al, 2017 ; Weuring et al, 2020 ). Due to their serious physiological effects and co-evolution of preys and predators, several Na v modulators including isoform-specific activators, are found in a variety of animal samples.…”
Section: Therapeutic Options For Sodium Channel Weakness Due To Na V 14 Loss Of Functionmentioning
confidence: 99%
“…By screening a Food and Drug Administration (FDA)-approved compounds library, clemizole has been identified as efficient to improve the epileptic phenotype resulting from Na v 1.1 haploinsufficiency on a zebrafish model for Dravet syndrome ( Baraban et al, 2013 ). Based on the fact that Na v 1.6 GoF results in severe epileptic phenotypes, two Na v 1.6 inhibitors have also been shown to improve the phenotype in another zebrafish model of Dravet syndrome with Na v 1.1 haploinsufficiency ( Weuring et al, 2020 ).…”
Section: Therapeutic Options For Sodium Channel Weakness Due To Na V 14 Loss Of Functionmentioning
confidence: 99%